POTENTIAL OF ALOE VERA GEL AS AN ALTERNATIVE INDUCTOR IN PLATELET AGGREGATION TEST - Gela Setya Ayu Putri; Andri Sukeksi (Jurnal Teknologi Laboratorium)
Platelet aggregation test is important in evaluation platelet function. Inductors are substances that stimulate the aggregation process. The use of ADP (adenosine diphosphate as an inductor has the disadvantage of being costly and difficult to obtain. Aloe vera is a plant from Africa which has been widely used for wound healing, therefore has the potential as an alternative inductor agent. This study aims to elucidate the effectiveness of Aloe vera gel as a platelet inductor compared to ADP reagent with the Velaskar method. This research started with the preparation of fresh Aloe vera to obtain Aloe vera gel. Then, venous blood was taken from 16 participants for platelet aggregation test. Platelet aggregation test was divided into two groups, namely ADP group (addition of ADP) and Aloe vera group (addition of aloe vera gel). The last step was analyze the results of platelet aggregation and statistically using the Independent Sample T-test. The average of percentage platelet aggregation with ADP and Aloe vera gel was 88.2 ± 5.6% and 85.7 ± 5.4%, respectively. Independent sample T-test analysis showed no significant difference between the percentage of platelet aggregation with ADP and Aloe vera gel. In conclusion, Aloe vera gel has the potential as an alternate platelet inductor. Some of the benefits of aloe vera gel are the ability to induce platelets as well as ADP, the application does not affect the morphology of erythrocytes, economical and practical (does not require elaborate preparation). Although the disadvantage is pure Aloe vera gel includes several components that able affect the performance of Aloe vera gel as an inductor.